Ductile mode turning of brittle materials and its practical aspects - Pramanik, Alokesh; Basak, A. (Trans Tech Publications Inc, 2013)
This paper aims to investigate the mechanism of ductile machining of brittle material based on information available in the literature. It also explores the challenges associated with the ductile machining of brittle materials which stop the technology from being applied in practical fields. In addition, few factors that assist to improve productivity of ductile machining of brittle material have been discussed. It is found the higher tool wear is the main obstacle of this technology. The application of micro-laser heating, ultrasonic vibration and coolants improve the machining time and tool life significantly.